Navigating the third wave: Contemporary UK feminist activists and 'third-wave feminism'. (August 2018) - Aune, Kristin; Holyoak, Rose
Since the start of the new millennium in the UK, a range of new feminist activities – national networks, issue-specific campaigns, local groups, festivals, magazines and blogs – have been formed by a new constituency of mostly younger women and men. These new feminist activities, which we term 'third-wave' feminism, have emerged in a 'post-feminist' context, in which feminism is considered dead or unnecessary, and where younger feminists, if represented at all, are often dismissed as insufficiently political. Representations of North American third-wave feminism are brought into play in these criticisms of the UK third wave, and insufficient attention has been paid to the distinctiveness of the UK contexts. Drawing on data from a survey of 1265 people involved in post-2000 forms of feminism and semi-structured interviews with thirty feminist activists, the article sketches out the contours of the contemporary feminist movement and its activists, activism and priorities. It attends to differences and similarities between second and third waves, and situates contemporary UK feminism in its distinctive UK context. Arguing that feminism is both alive and relevant for significant numbers of people in the UK today, the article interrogates younger feminists' reluctance to use the term 'third-wave feminism' to describe themselves, attributing this reluctance to ambivalent and cynical representations of the third wave in academic literature and the popular media.